All-fiber arbitrary and precise pulse spectral shaping. (20th March 2015) - Wang, Shiwei; Zheng, Wanguo; Zhao, Lei; Zhu, Qihua; Xu, Jianqiu; Tang, Yulong
Abstract: A fiber-loop-based electro-optic (EO) modulation system is proposed and demonstrated to realize both broadband and high-resolution spectral shaping of laser pulses through direct phase modulation. With this fiber-loop EO modulator, arbitrary spectral shape can be carved and the modulation precision is up to 0.004 nm. The laser spectral bandwidth can be steadily broadened from several MHz to several nanometers through tuning the pulse cycle times and the programmable driving signal. One representative shaped spectrum is presented with a <0.01 nm mismatch to the simulated results, which is used to effectively pre-compensate the pulse spectral distortion during amplification.